Demand For Smoking in Iran - Teimor Mohamadi; Leila Hoseini (فصلنامه پژوهش‌های اقتصادی ایران, 2010)
This  paper   surveys theoretical  foundation  and   empirical   results of demand for  smoking: Theoretical foundation  is  based  on  a model of habit effects .Empirical results is based on a regression for smoking demand in Iran for the period 1363-1379 (1984-2000). The quantity demanded is determinded by price ,income ,literacy, unemployment and divorce  rates .The  elasticity of demand with  respect to first four variables are -0.27, 0.44, 0.2   and  -2.54, respectively.The  divorce  rate is not significant.Thus cigarette  is an inelastic  and normal necessity  good. Also, the significant coefficient of the quadratic  term of income confirms the satiation effect. Accordingly, prohibitive policies based on price are not successful  and  it is necessary  to  make a shift to  non- price measures.